2021
DOI: 10.1186/s13046-021-01938-2
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy-induced CDA expression renders resistant non-small cell lung cancer cells sensitive to 5′-deoxy-5-fluorocytidine (5′-DFCR)

Abstract: Background Pemetrexed (MTA) plus cisplatin combination therapy is considered the standard of care for patients with advanced non-small-cell lung cancer (NSCLC). However, in advanced NSCLC, the 5-year survival rate is below 10%, mainly due to resistance to therapy. We have previously shown that the fraction of mesenchymal-like, chemotherapy-resistant paraclone cells increased after MTA and cisplatin combination therapy in the NSCLC cell line A549. Cytidine deaminase (CDA) and thy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 60 publications
1
9
1
1
Order By: Relevance
“…Contrary to our expectation, immunohistochemistry of CDA showed no significant difference between pre-and post-ALK inhibitor therapy (Fig. 6e, left), which might be attributable to inter-or intratumoral heterogeneity of CDA expression even in the same patient 38 . Representative CDA expression in tumors from pre-or post-TKI therapy is shown in Fig.…”
Section: Clinical Relevance Of Cda In Lung Cancer Patientscontrasting
confidence: 99%
“…Contrary to our expectation, immunohistochemistry of CDA showed no significant difference between pre-and post-ALK inhibitor therapy (Fig. 6e, left), which might be attributable to inter-or intratumoral heterogeneity of CDA expression even in the same patient 38 . Representative CDA expression in tumors from pre-or post-TKI therapy is shown in Fig.…”
Section: Clinical Relevance Of Cda In Lung Cancer Patientscontrasting
confidence: 99%
“…Visual examination revealed that a significant fraction of the cells had changed their morphology after treatment, namely, increased cell size and granularity, which is reminiscent of the induction of cellular senescence, as we have shown previously [ 3 , 4 , 9 ]. To confirm the induction of senescence, cells were reseeded at low density 6 days after therapy (day 10, see Figure 1 B).…”
Section: Resultssupporting
confidence: 65%
“…The acquisition of a senescence phenotype is also associated with an increase in cell size and granularity (reviewed in [ 14 ]), which can be quantified by flow cytometry as an increase in the intensity of forward (FSC) and side scatter (SSC), respectively [ 9 , 15 ]. Indeed, the fraction of cells characterized by increased FSC and SSC intensity (F/S-high) was already maximally increased during the treatment phase of concomitant therapy (day 3), whereas the peak in the frequency of F/S-high cells was only reached on day 7 and day 10 after 24 h and 48 h of MTA treatment, respectively ( Figure 2 C,D).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although alkylating agents and radiation exposure have anti-cancer effects, therapeutic resistance is common (1,2). Previous studies have shown that these approaches can effectively increase cell apoptosis, DNA damage, and proliferation inhibition (3).…”
Section: Introductionmentioning
confidence: 99%